Дефектоскопический бетатрон на энергию 9 МэВ; Контроль. Диагностика; № 9 - Волков В. Г. Владимир Григорьевич; Звонцов А. А. Александр Акимович; Зрелов Ю. Д. Юрий Дмитриевич; Касьянов В. А. Валерий Алексеевич; Касьянов С. В. Станислав Валериевич; Филимонов А. А. Анатолий Алексеевич; Штейн М. М. Михаил Михайлович (2013, 2013)
Заглавие с экрана